MEASUREMENT OF R AND SEARCH FOR THE TOP QUARK IN E+E- ANNIHILATION BETWEEN 39.8 AND 45.2 GEV - Althoff, M; Braunschweig, W; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Peise, G; Rimkus, J; Rosskamp, P; Sander, H; Schmitz, D; Siebke, H; Wallraff, W; et al. (1984)
e+e- annihilation into hadrons was studied at CM energies between 39.8 and 45.2 GeV and a search was made for new heavy quarks. No evidence was found for the existence of a narrow state excluding the possible existence of the lowest vector toponium state in this mass range. A search for continuum production of heavy quarks led to lower mass limits for new quarks of 22.0 GeV (eQ = 2 3) and 21.0 GeV (eQ = 1 3). Quarks are found to be pointlike, the corresponding mass parameter being larger than 288 GeV. A fit of the QCD and the electroweak contributions to R=σtot/σμμ yielded sin2θW = 0.30-0.07+0.23. © 1984.